2020
DOI: 10.1002/aepp.13011
|View full text |Cite
|
Sign up to set email alerts
|

Improving Gender Participation in Agricultural Technology Adoption in Asia: From Rhetoric to Practical Action

Abstract: New and improved agricultural technologies can transform lives, particularly the lives of smallholder farm households in Asia who are highly dependent on agriculture. However, there are large gender disparities in the adoption of such technologies. Many barriers exist in achieving gender equity in access to and adoption of agricultural technologies, from sociocultural norms and deeply rooted beliefs about gender roles to lack of agency and lack of resources to implement policies. Notwithstanding these barriers… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
25
1

Year Published

2020
2020
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 66 publications
(31 citation statements)
references
References 36 publications
2
25
1
Order By: Relevance
“…The challenges faced are particularly great for women smallholders. Rola‐Rubzen et al () describe gender‐specific barriers to adoption and highlight the potential gains from breaking these barriers.…”
Section: Methodological Issuesmentioning
confidence: 99%
See 1 more Smart Citation
“…The challenges faced are particularly great for women smallholders. Rola‐Rubzen et al () describe gender‐specific barriers to adoption and highlight the potential gains from breaking these barriers.…”
Section: Methodological Issuesmentioning
confidence: 99%
“…Supporting women farmers. Discrimination and lack of access to technology and resources reduce women's capacity to contribute to agricultural productivity, resulting in significantly negative social welfare outcomes (Rola-Rubzen et al 2020). Elimination of discrimination in access to credit, ownership of resources, access to activities that they can perform and education should be policy priorities, particularly in developing countries.…”
Section: Implications For Policymentioning
confidence: 99%
“…Research has shown that gender bias can constrain agricultural productivity (Jafry and Sulaiman ; Quisumbing et al ), a fact that extension services seemed largely unaware of four decades ago. Today, extension services in many countries function with greater gender balance in reaching out to male and female decision makers, although additional progress is needed (Quisumbing et al ; Rola‐Rubzen et al ).…”
Section: Extension Changesmentioning
confidence: 99%
“…Mwangi and Kariuki 2015) so are not proposed as additional factors here. However, it is recognized that gender can be an important factor influencing adoption in some cases (Rola-Rubzen et al 2020). In these cases, policy makers may consider evaluating adoption for gender-based subpopulations, as gender can influence a range of factors with consistent influence on adoption, such as information access (Mwangi and Kariuki 2015;Brown, Llewellyn, and Nuberg 2018a).…”
Section: Additional Considerations For Predicting Adoption In Smallhomentioning
confidence: 99%